Regional Police Cooperation in Combating Transnational Crime in Southeast Asian Region - Phoophanichjaroenkul, Suphat (วารสารเอเชียตะวันออกและอาเซียนศึกษา, 2023)
This article examines the susceptibility of Southeast Asian countries to transnational crime, primarily due to the permeable borders resulting from their small landmass and comparatively large population. Each nation adopts a distinct approach in combating prevalent types of crime within its respective region. Moreover, the article delves into the formidable challenges faced by law enforcement agencies in this area, including language barriers, inadequate transnational coordination, limited resources, and the complex issue of cooperation among police forces in the Southeast Asian Region, particularly the ASEAN National Police or ASEANAPOL. The present study employed a qualitative approach, utilizing descriptive analysis methods to gather primary and secondary sources, including statutes, legislation, international agreements or treaties, as well as academic articles from law textbooks or legal journals. Then, the article will analyse the rise of transnationalization of crime alongside the establishment of the ASEAN Political-Security Community, which aims to eradicate transnational crime and enhance public safety within the region. Subsequently, it will explore the collaborative efforts among police forces at the international, regional, and bilateral levels to effectively address transnational crimes and facilitate the sharing of pertinent information. Lastly, it will assess the role of the ASEAN National Police or ASEANAPOL, a regional police conference that endeavours to develop strategies for combatting various forms of transnational crimes, in comparison with Interpol and Europol.